Use of Insecticide-Treated Mosquito Net among Pregnant Women and Guardians of Children under Five in the Democratic Republic of the Congo. (6th November 2017) - Inungu, Joseph N.; Ankiba, Nestor; Minelli, Mark; Mumford, Vincent; Bolekela, Dido; Mukoso, Bienvenu; Onema, Willy; Kouton, Etienne; Raji, Dolapo
Abstract : Background . Insecticide-treated mosquito nets (ITNs) are one of the most effective tools for preventing malaria in sub-Saharan Africa. Objective . This study examined knowledge, attitude, and practice on the use of ITNs in the prevention of malaria among pregnant women and guardians of children under five in the Democratic Republic of the Congo. Methods . A total of 5, 138 pregnant women and guardians of children under five were interviewed. Results . The majority of participants (>80%) knew the signs and symptoms of malaria; 81.6% reported having an ITN in the household, but 78.4% reported using it the night before the interview. Only 71.4% of pregnant women used ITN the night compared to 68.2% of children under five. In the Logistic Regression model, women who believed that it is normal to use ITNs were 1.9 times more likely to use it than those who did not (OR: 1.930); women who were confident in their abilities to use ITNs were 1.9 times more likely than those who were not confident (OR: 1.915); and women who had a good attitude towards ITNs were also more likely to use ITNs compared to those who did not (OR: 1.529). Conclusion . New and innovative evidence-based behavior change interventions are needed to increase the utilization of ITNs among vulnerable groups.